The fate of antibiotics and anticancer drugs in the aquatic environment - Evaluating the photolysis of ciprofloxacin and monitoring the course of its genotoxicity by a combination of experimental and in silico testing - Haddad, Tarek (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2016)
After being administrated to humans or animals, pharmaceuticals may be metabolized by a variety of mechanisms and pathways within the body. Once these compounds and/or their metabolites are excreted, they may undergo degradation in the aquatic environment. Unfortunately, a rapid and complete mineralization cannot always be guaranteed, whereas relatively stable transformation products (TPs) may be formed. The largest part of older studies focused on investigation of the elimination kinetics of parent compounds without considering the amount and chemical structure of individual TPs. Only recently, there is an increasing trend to deliver such information. Nevertheless, since drugs are defined as significant environmental pollutants, it is not only important to elucidate their TPs, but also necessary to investigate whether these formed compounds preserve the same mode of action as the parent compound or are even more toxic. Thus, two main objectives of this thesis can be formulated. Firstly, to highlight the concern originated by metabolites and transformation products of pharmaceuticals that contaminate the environment. Hereby, the already-published knowledge on TPs within a certain selection of drugs is assessed to exemplify the number and quality of the existing information on their TPs. Secondly, to particularly investigate the fate of the antibiotic ciprofloxacin (CIP). This is done by (a) evaluating the suitability and sustainability of the photolytic decomposition as an advanced water treatment technique, (b) monitoring the course of genotoxicity of the irradiated mixtures using a battery of genotoxicity and cytoxicity in vitro assays, and (c) considering the potential genotoxicity for CIP´s individual TPs by the employment of in silico approaches using quantitative structure activity relationships (QSAR) models. This thesis based on the results and conclusions of five articles, which can be found in the appendix. A systematic literature review was conducted on the current state of knowledge on pharmaceuticals and its derivatives in the environment. Two groups, namely antibiotics and anticancer drugs, were considered more closely with respect to the availability of chemical structures for their TPs. Furthermore, the photodegradation of CIP as well as a preliminary toxicity assessment of its identified TPs were investigated in three research papers. An extensive review with a table at its core shows the existing data on 158 TPs, which already have an assigned registry number in chemical abstracts service (CAS-RN), was presented. In total, 294 TPs, identified with chemical structures in the literature, were found for 15 compounds out of the 21 that were selected as target compounds. Eleven TPs, created from CIP, were identified by high-performance liquid chromatography/high-resolution multiple-stage mass spectrometry. It was detected that the transformation of CIP mainly occurred through substitution of fluorine, defluorination, hydroxylation of the quinolone core and the breakdown of the piperazine ring. Some of the identified TPs of CIP were predicted as genotoxic by QSAR analysis, while the experimental testing for a few genotoxic and cytotoxic endpoints showed that the potential of the resultant mixtures could be primarily dependent on the concentration of residual CIP. In contrast, irradiation mixtures were neither mutagenic in the Ames Test nor genotoxic in the in vitro Micronucleus Test. It is possible that the effect of the TPs was masked by antagonistic mixture interactions and/or they were not formed at effectively concentrations. Nevertheless, all of the identified TPs of CIP still retained the core quinolone moiety, which is responsible for the biological activity. Thus, a more comprehensive assessment, encompassing more genotoxic endpoints, chemical analysis characterization and exposure analyses, needs to be conducted. Information available on TPs demonstrates that already slight changes in treatment conditions and processes result in the formation of different TPs. Nevertheless, most of the transformation products could neither be identified nor fully assessed regarding their toxicity. This, in turn, presents a major challenge for the identification and assessment of TPs. Hence, from a practical and sustainability point of view, limiting the input of pharmaceuticals into effluents as well as improving their (bio)degradability and elimination behavior, instead of only relying on advanced effluent treatments, is urgently needed. Solutions that focus on this

Auf den Einsatz von Arzneimitteln folgt meist ein nur unvollständiger Abbau der Wirkstoffe im Körper von Mensch oder Tier. Somit werden die entsprechenden Ausgangssubstanzen und ihre Metabolite ausgeschieden und gelangen in das Abwasser. In der aquatischen Umwelt und/oder während der Abwasserbehandlung kommt es dann sehr häufig nicht zu einer vollständigen Mineralisierung, sondern zur Bildung mehr oder weniger stabiler Transformationsprodukte (TPs). Entsprechende Studien konzentrieren sich größtenteils auf die stattfindende Abbaukinetik ursprünglicher Wirkstoffe, ohne dabei auf die tatsächlichen chemischen Strukturen oder die Menge der entstehenden TPs einzugehen. Lediglich in neuesten Studien zeichnet sich ein Trend ab, auch diese Informationen zu präsentieren. Da Medikamente maßgeblich zur Kontamination der Umwelt beitragen, ist es weiterhin von außerordentlicher Wichtigkeit, nicht nur die Transformationsprodukte selbst, sondern auch ihre diesbezügliche potenzielle Wirkung zu benennen. Transformationsprodukte können unter Umständen dieselben oder gar toxischere Auswirkungen auf Organismen haben als ihre Muttersubstanz. Die entsprechenden Hauptziele dieser Arbeit lassen sich in zwei Teile gliedern: Der erste Teil befasst sich mit den Umweltauswirkungen, die von Arzneimitteln, Metaboliten und ihren TPs ausgehen können, und präsentiert dann für eine Auswahl von Medikamenten eine bewertende Zusammenfassung der bereits publizierten Informationen zu ihren jeweiligen Transformationsprodukten. Der zweite Teil umfasst weiterführende Untersuchungen zu dem Antibiotikum Ciprofloxacin (CIP), nämlich: a) eine Bewertung der Effektivität des photolytischen Abbauprozesses im Labor, b) die Identifizierung von Abbauprodukten und c) eine vorläufige Einschätzung potenzieller Auswirkungen auf die Umwelt (z.B. bakterielle Toxizität, Mutagenität und Genotoxizität mit experimentellen Systemen sowie computerbasierten Methoden, wie
Das Verhalten von Antibiotika und Zytostatika in der aquatischen Umwelt: Bewertung der Effektivität des photolytischen Abbauprozesses von Ciprofloxacin und eine vorläufige Einschätzung potenzieller Genotoxizität mit experimentellen Systemen sowie computerbasierten Methoden
Keywords: Photolysis; Pharmaceuticals; Water Treatment; Arzneimittel; Wasserbehandlung; 540 Chemie und zugeordnete Wissenschaften